The auditory stimulus facilitates memory guidance in distractor suppression in males with substance use disorder - Cai, Biye; Wang, Jinjin; Sang, Hanbin; Zhang, Zonghao; Wang, Aijun (Frontiers in Psychology, 2024)
Introduction Representations in working memory can affect distractor suppression in human visual search, and this process is modulated by a separate top-down cognitive control. An increasing body of research has demonstrated that patients with substance use disorder (SUD) have deficits in cognitive control over filtering interference by perceptual distractors. However, their ability to resist proactive interference from working memory has received comparatively less attention. Methods Here, we investigate this issue by employing a working memory/visual search dual-task paradigm. An intervening gap-location search task was instructed to be performed while participants memorized a written color word, with congruent auditory information present during the memory encoding phase on half of the trials. Results Results showed that there was a reliable response time (RT) advantage when the meaning of the memory sample agreed with the color of one of the distractors under the visual alone condition. However, such a result was only found in the control group. More importantly, both groups exhibited comparable facilitation under the audiovisual condition, with the facilitation effect appearing later in the SUD group. Furthermore, the facilitation effect was superior in magnitude and time course under the audiovisual condition to the visual alone condition. Discussion These findings highlight how patients with SUD resist distractor interference at the memory level and extend our understanding of how working memory, selective attention, and audiovisual enhancement interact to optimize perceptual decisions in patients with SUD.